Research Into Biological Characterictics of Dried Sapropel (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
Microbiological characteristics of dried sapropel of Lake Rušona and Lake Ubagova and concrete containing sapropel and hemp sheaves (Ubagova Lake) have been studied. The antimicrobial activity was studied by thereference test culturesStaphylococcus aureus  ATCC 25923, Salmonella enteritidis ATCC 13076, Enterococcus faecalis  ATCC 29212, Bacillus cereus  ATCC 10876, Escherichia coli ATCC 25922, Candida albicans ATCC 10231. Antibacterial activity on Staphylococcus aureus reference test cultures is stated in Rušona Lake sample before treatment with UV rays. Antibacterial activity is not stated in Ubagova Lake sapropel sample. 20 minutes’ long UV ray treatment is not long enough to prevent the growth of sapropel materials. Both Rušona Lake and Ubagova Lake samples contain microorganisms that start growing and intensively reproducing in favourable conditions. When in contact with humidity, at the temperature from 18 to 37± 1 0C, mold colonies form on concrete containing sapropel and hemp sheaves, for this reason this material should not get in contact with humidity when used in construction.